Effect Of Zn Addition On Microstructure, Intermetallic Compound Formation And Mechanical Properties Of Sn-0.7cu Solder On Cu Substrate - Ghani, Fitriah Abdul (2018)
Solder joints serve as both electronic and mechanical connections between components as well as substrates in electronic devices. Concern over the toxicity of lead sparked intense focus on finding alternative lead-free solders to replace the traditional Sn-Pb solder. An attractive candidate is Sn-Cu alloy as it is cheaper than Ag-containing solders. However, Sn-0.7Cu has been reported to have lower strength than the other lead-free solders. There is potential to further improve the performance of Sn-0.7Cu and increase solder joint reliability especially for high-powered solder joints. In this study Sn-0.7Cu, Sn-0.7Cu -0.5Zn and Sn-0.7Cu -1.0Zn bulk solder alloys were developed. The addition of Zn potentially refines solder microstructure and results in secondary particles that could strengthen the solder. Alloying of Zn also has been reported to decrease thickness of Cu-Sn IMC layer in Sn-based solder alloys. Characterization of the solder alloys focused on the bulk solder microstructure and IMC evaluation. Melting point of solder was determined using Differential Scanning Calometry (DSC) while elemental composition of solders were analysed using X-ray fluorescence (XRF). Aging was done for 100, 200 and 500 hours at 150 °C and 180 °C. Microstructure of bulk solder and the IMC formed at interface between solder and Cu substrate were observed using SEM equipped with EDX. Addition of Zn slightly decreased the wettability compared to Sn-Pb, but still having good wettability because all the wetting angle are in range of 34°to 38°. Results showed that wettability reduced with increasing amount of Zn but the hardness was increased. The addition of Zn also showed increased shear strength up to 40% higher than that of the Sn-Cu solder alloys.